Symptom burden and health-related quality of life impacts of smoldering multiple myeloma: the patient perspective - Milenka Jean-Baptiste; Katharine S. Gries; William R. Lenderking; John Fastenau (SpringerOpen, 2020)
Abstract Background Smoldering multiple myeloma (SMM) is an early form of multiple myeloma (MM). SMM is typically considered asymptomatic, and research on how it affects health-related quality of life (HRQoL) is limited. This study assessed the symptoms and HRQoL of patients with SMM and those who progressed from SMM to MM and evaluated the content validity of two patient-reported outcome instruments (EORTC QLQ-C30 and nine items from the EORTC QLQ-MY20) for use in SMM clinical trials. To address these objectives, concept elicitation and cognitive interviews were conducted with SMM patients and recently diagnosed MM patients. Results Fifteen adult SMM and six adult MM participants with a prior SMM diagnosis were interviewed. On average, SMM study participants were 61 years old (46.0-78.0), 11 (73%) were female, and diagnosed 2.6 (±2.0) years ago. Each participant had experienced at least one symptom, most commonly tiredness/fatigue, weakness, and pain. The most common HRQoL impacts were emotional and physical. SMM study participants demonstrated good understanding of both the EORTC QLQ-C30 and EORTC QLQ-MY20 subscales and found them relevant to their SMM health state. The average age of MM participants was 53 years old (39.0-62.0); 5 (83%) were female and diagnosed 1.9 years ago (±2.1). MM participants most commonly reported tiredness, weakness, constipation, shortness of breath, and dry mouth as occurring when they progressed from SMM to MM. Conclusions Although previously described as asymptomatic, these SMM participants reported experiencing symptoms that affected their lives. Additionally, the EORTC subscales measured symptoms SMM patients experienced. The participants with MM reported that the symptom burden and HRQoL impacts increased when diagnosed with MM. These findings suggest the need for increased surveillance of symptoms within the SMM population and further suggest that the EORTC subscales can be used to assess symptoms and impacts in both the SMM and MM populations.